The Cultural Formulation Interview as a clinical tool in the assessment of eating disorders: a pilot study - Strand, Mattias; Welch, Elisabeth; Bäärnhielm, Sofie (Frontiers in Psychiatry, 2024)
Background: The Cultural Formulation Interview (CFI) in the DSM-5 is a person-centered instrument for systematically appraising the impact of sociocultural factors in psychiatric assessment. The CFI has been shown to be feasible, acceptable, and useful in various clinical contexts. However, to this date there is only one published report describing the use of the CFI with patients with eating disorders. Aims: To explore the potential benefits and challenges of utilizing the CFI in the assessment of eating disorders. Methods: As an addendum to an ongoing qualitative study about barriers to treatment for eating disorders for individuals with a migration background in Sweden, we utilized the CFI in the assessment of adult patients (n=8) in specialist eating disorder treatment. Interview data were analyzed employing a thematic analysis framework. Participants provided feedback using a standard form for evaluation of the CFI. Results: Certain CFI questions proved especially meaningful in this context. In response to the CFI question about patient explanatory models, previously unrecognized ideas about causation emerged. These included perfectionism—a known risk factor for eating disorders—based on immigrant parents’ career expectations and experiences of strict family control over life choices. In response to the CFI questions on cultural identity and its impact, the participants provided rich descriptions including important themes such as religion, racism, and ambiguities associated with being a second-generation immigrant. The final CFI question, eliciting concern about the patient-clinician relationship, revealed numerous examples of prejudice and unfamiliarity with migrant groups among healthcare providers. The participants rated the CFI as a feasible, acceptable, and clinically useful instrument. Implications: The CFI can be useful in the assessment of patients with eating disorders and should be further explored as a standard tool in specialist eating disorder services.